2016
DOI: 10.3892/ol.2016.4722
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of sonic hedgehog-Gli signaling: A potential therapeutic target for patients with breast cancer

Abstract: Abstract. Breast cancer is the most common malignant cancer among women. The Hedgehog (Hh) signaling pathway serves a key role in malignant cancer cell growth and migration. However, little is known with regard to the specific function of the Hh signaling pathway in human breast cancer. The current study investigated the specific role of Hh signaling in the human breast cancer cell line MDA-MB-231. Expression of components of Shh-Gli signaling, as well as the Gli-responsive genes B-cell lymphoma 2 (Bcl-2) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…The Shh signaling pathway plays crucial roles in regulating cell differentiation, adhesion, migration, transformation, and apoptosis [ 19 ]. It was found that Shh signaling was activated in many human cancers such as gastric cancer, liver cancer, breast cancer, and ovarian cancer [ 11 , 20 ]. Moreover, activation of Shh signaling was found to be highly associated with increased capacities of chemoresistance and radioresistance in human malignant tumors [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Shh signaling pathway plays crucial roles in regulating cell differentiation, adhesion, migration, transformation, and apoptosis [ 19 ]. It was found that Shh signaling was activated in many human cancers such as gastric cancer, liver cancer, breast cancer, and ovarian cancer [ 11 , 20 ]. Moreover, activation of Shh signaling was found to be highly associated with increased capacities of chemoresistance and radioresistance in human malignant tumors [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Then Smo perform translocation and thereby activates downstream transcriptional factors of the glioma-associated oncogene homolog (Gli) family to which Shh belongs, including Gli1, Gli2, and Gli3 [ 10 ]. Gli1 is the most important member, which translocates to the nucleus after activation and further initiates transcription of target genes regulating cell cycle, apoptosis, migration, and signaling transductions [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant activation of the Sonic hedgehog (Shh; the vertebrate counterpart of Hh) signaling pathway has been implicated in initiation, progression, and metastatic invasion of multiple cancer types (Evangelista et al 2006;Song et al 2016). While deregulated Shh signaling upregulates levels of different components of cell-cycle machinery leading to unrestricted proliferation of cancer cells (Kenney and Rowitch 2000;Mille et al 2014), Shh signaling also promotes metastasis through induced expression of MMP-2 and MMP-9 (Wang et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In MDA-MB-231 TNBC cells, a marked increase in the levels of the activated Sonic Hh (SHh), Ptch, Smo and Gli1 resulted in overexpression of Bcl2 and cyclin D1, thereby contributing to cell proliferation and survival [ 305 ]. Cyclopamine treatment in these cells resulted in a decrease in Gli mRNA and cell viability which correlated with the cyclopamine treatment-associated decrease in Bcl2 and cyclin D1 [ 305 ]. Additionally, exposure of MDA-MB-231 cells to human SHh significantly reduced the levels of E-cadherin, increased MMP2 and MMP9, and enhanced cell migration and invasion, thereby contributing to EMT.…”
Section: Phytochemicals As Anticancer Compounds Effective In the Tmentioning
confidence: 99%
“…Additionally, exposure of MDA-MB-231 cells to human SHh significantly reduced the levels of E-cadherin, increased MMP2 and MMP9, and enhanced cell migration and invasion, thereby contributing to EMT. This effect was reversed, and levels of E-cadherin were enhanced, while the levels of MMP2 and MMP9 decreased in cyclopamine treated cells, with a consequent decrease in cell migration and invasion [ 305 ]. Cyclopamine treatment showed significant suppression of proliferation in MCF-7 and MDA-MB-231 breast cancer cells, caused by a robust G1 cell cycle arrest and inhibition of MAPK/ERK signaling which contributed to the decrease in the expression of cyclin D1 [ 188 ].…”
Section: Phytochemicals As Anticancer Compounds Effective In the Tmentioning
confidence: 99%